Coupling Driving Force–Pressure–State–Impact–Response–Management Framework with Hydrochemical Data for Groundwater Management on Sithonia Peninsula, Greece - Eleni Parastatidou; Maria Margarita Ntona; Nerantzis Kazakis; Fotios-Konstantinos Pliakas (Geosciences)
Water scarcity in coastal tourist areas constitutes a critical environmental and socioeconomic sustainability issue. Hence, it is crucial to implement an integrated water resource management and protection plan. In this research, the DPSIR framework is coupled with hydrochemical data on groundwater resources in the fractured aquifer of the Sithonia Peninsula in Chalkidiki, North Greece. Geographical and demographic data, together with morphology, geology, hydrology, and groundwater quality data, were collected and evaluated to categorize the hydrosystem’s driving forces, pressures, states, impacts, and responses. The main pressures that affect groundwater quality in the study area are tourism, geological formation, and land use. Based on the analysis of the DPSIR framework, the absence of a landfill site, the inadequate operation of sewage treatment plants and biological wastewater treatment systems, and tourist activity contribute significantly to the degradation of groundwater quality. Additionally, the fractured rock aquifer develops preferential flow paths to pollutants through preexisting faults, which influence groundwater quality. The hydrochemical analysis of groundwater indicates seawater intrusion in the coastal area. The combination of DPSIR analysis and a water quality index based on ion ratios of groundwater samples identifies high-risk areas of seawater intrusion. Thus, it is essential to reinforce groundwater resources by implementing managed aquifer recharge, limiting unnecessary use of groundwater during the tourist season, and storing surface water during the wet period.